2009
DOI: 10.1007/s11095-009-9975-2
|View full text |Cite
|
Sign up to set email alerts
|

Long- and Short-Range Electrostatic Interactions Affect the Rheology of Highly Concentrated Antibody Solutions

Abstract: This discrepancy occurs because long-range interactions are significant at low concentrations, whereas both long- and short-range interactions are significant at higher concentrations. Computer modeling was used to calculate antibody properties responsible for long- and short-range interactions, i.e. net charge and dipole moment. Charge-charge interactions are repulsive while dipole-dipole interactions are attractive. Their net effect correlated with the storage modulus profile. However, only charge-charge rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
141
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(149 citation statements)
references
References 39 publications
3
141
0
Order By: Relevance
“…This behaviour is consistent with the increase in the k D value for 5E when adding sodium chloride. Previous studies have found a strong correlation between increased aggregation rates and electrostatic selfassociation [13,55,80,99], which might also explain the increased aggregation of 5E.…”
Section: The Patch-charged Mutantsmentioning
confidence: 82%
See 1 more Smart Citation
“…This behaviour is consistent with the increase in the k D value for 5E when adding sodium chloride. Previous studies have found a strong correlation between increased aggregation rates and electrostatic selfassociation [13,55,80,99], which might also explain the increased aggregation of 5E.…”
Section: The Patch-charged Mutantsmentioning
confidence: 82%
“…However, care must be taken when engineering in charged mutations. If the protein net charge is close to zero, an anisotropic charge distribution can cause protein self association [13,14,71,99], which has been correlated with increased aggregation propensity [55,80]. To avoid increasing protein charge anisotropy, charged mutations should carry the same sign as the net charge on the corresponding protein scaffold [31,100].…”
Section: Introductionmentioning
confidence: 99%
“…The foregoing moderate viscosity reductions of inorganic salts suggest that electrostatic interactions (Chari et al, 2009), in general, were not of a major importance in concentrated protein solution's viscosity. Therefore, we hypothesized that hydrophobic protein-protein interactions instead were predominantly responsible for the reversible protein aggregates in concentrated solutions creating resistance to flow and, in turn, leading to high solution viscosity.…”
Section: Resultsmentioning
confidence: 99%
“…52 Similar trends in viscosity in response to changes in solution conditions that we describe here for mAb-C have been reported for other IgG1 mAbs, where the extent of viscosity increased in a concentration-dependent manner with increasing ionic strength 11,18,30,53,54 and solution pH, 11,55 related to elevated levels of protein RSA due to charge shielding effects. [56][57][58] The isoelectric point (pI) range of mAb-C is basic (pI»9.1-9.4), 45 and therefore, the overall surface charge of mAb-C is expected to be positive at neutral pH. As the pH was changed from 6 to 8, the tendency of mAb-C to self-associate increased, possibly due to overall decrease in electrostatic repulsive interactions.…”
Section: Discussionmentioning
confidence: 99%